2019
DOI: 10.12998/wjcc.v7.i20.3372
|View full text |Cite
|
Sign up to set email alerts
|

Ureteral Ewing’s sarcoma in an elderly woman: A case report

Abstract: BACKGROUNDEwing’s sarcoma (ES) is regarded as a skeletal tumor, with few instances of extra-skeletal ES. A primary ES in the ureter is extremely rare.CASE SUMMARYWe report the case of a 69-year-old woman who presented with intermittent flank pain and hematuria and was found to have a mass in the left ureter. Pathology of the excised mass indicated ES. The clinical treatment and pathologic characteristics in this case, and a review of the literature describing ES in the urinary system, are presented.CONCLUSIOND… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…A review of the English-language literature revealed that the urogenital tract is rarely involved: the most common site is the kidney, with almost 200 cases described ( 7 , 8 ), followed by the bladder ( 9 ), and the prostate ( 10 , 11 ). Ureteral localization is an exceptional finding, with only four cases of primary ES of the ureter previously reported ( 12 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A review of the English-language literature revealed that the urogenital tract is rarely involved: the most common site is the kidney, with almost 200 cases described ( 7 , 8 ), followed by the bladder ( 9 ), and the prostate ( 10 , 11 ). Ureteral localization is an exceptional finding, with only four cases of primary ES of the ureter previously reported ( 12 15 ).…”
Section: Discussionmentioning
confidence: 99%
“…Remarkably, due to the lack of a preoperative histological diagnosis, three of the four previously reported cases received chemotherapy only after surgery ( 12 – 14 ). In one patient, a 69-year-old woman, systemic therapy was not administered due to age and impaired cardiopulmonary function ( 15 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although not the focus of this discussion, it is worthwhile to note that several cases of primary Ewing's sarcoma in both children and adults within the bladder, ureter and kidney have been reported and treated with a combination of surgical resection, chemotherapy and radiation [20][21][22][23].…”
Section: Discussionmentioning
confidence: 99%